Spanglish en los Estados Unidos: Apuntes sobre lengua, cultura e identidad - Silvia Betti (Confluenze, 2009)
This study presents some thoughts on the usage of so called "Spanglish" language in the United States. Its aim is that of looking at the potential facilitative effect the usage of Spanglish has in helping Hispanic and Anglo- Saxon speakers, who do not share either English or Spanish, to achieve communicative goals in particular communicative contexts. The literature has acknowledged that Spanglish relies on code-switching and code-mixing, switches and mixtures which can also be described as characteristics of the hybrid identity of many Latinos in the United States. In this paper we do not get into the details of the peculiarities of national identities (i.e. Cubans, Dominican Americans, Mexicans, Puerto Ricans and the like), we rather propose to look at the phenomenon of Spanglish in its hybrid aspect, which is what, in our view, makes it complex and fascinating from the perspective of mixed identities in intercultural contexts.